Italian COVID-19 epidemic: effects on paediatric emergency attendance—a survey in the Emilia Romagna region - Federico Marchetti; Giacomo Biasucci; Andrea Cella; Lorenzo Iughetti; Anna Rita Di Biase; Giulia Graziani; Alessandro De Fanti; Enrico Valletta; Francesca Vaienti; Gianluca Vergine; Laura Viola (BMJ Paediatrics Open)
Objective To evaluate the effect of the COVID-19 epidemic on paediatric emergency department (ED) attendance in a region of Northern Italy.Methods A survey was proposed to six out of nine paediatric EDs in the Emilia Romagna region to evaluate attendance data, distribution by age and gender, triage code score, outcome of clinical course, number of hospitalisations and the distribution of patients by disease. Data were collected during March 2020 and compared with that of March 2019.Results A drop in paediatric ED attendance of more than 83.8% was observed, with a higher percentage of infants and severe triage scores. The proportion of patients hospitalised was significantly higher in 2020 than in 2019 (p value: <0.001). The effect size for the comparison of proportions of hospitalised patients was 0.379. Looking at the distribution of attendance by type of disease, a significantly different distribution was highlighted (p value: <0.00001, Cramer’s V); there was a greater proportion of patients presenting to paediatric EDs with poisonings (effect size=0.07), psychiatric pathologies (effect size=0.110), head injuries (effect size=0.167) and fever (effect size=0.212).Conclusions Our survey suggests that in the first month of the COVID-19 epidemic in Italy, there has been an increase in delayed attendance and provision of care of potentially severe diseases in paediatric EDs. Hospital and community paediatricians should be aware of this phenomenon and adopt appropriate strategies to prevent this danger, as it may affect children more seriously than COVID-19 itself.